적립계 장수형 붉은곰팡이병 중도저항성 제면용 밀(Triticum aestivum L.) ‘태중’ - 김경민(Kyeong-Min Kim); 김경훈(Kyeong-Hoon Kim); 정영근(Young-Keun Cheong); 최창현(Chang-Hyun Choi); 김양길(Yang-Kil Kim); 박종호(Jong-Ho Park); 김경호(Kyong-Ho Kim); 장지선(Jiseon Jang); 최진경(Jin Kyung Choi); 배정숙(Jeong-Suk Bae); 민병규(Byeong-Kyu Min); 김승남(SeungNam Kim); et al. (Korean journal of breeding, 2019)
A new winter wheat (Triticum aestivum L.) cultivar, “Taejoong”, was developed by the National Institute of Crop Science, Rural Development Administration in 2016. It was derived from a cross between “Xian83(104).11” and “Keumkang” in 2005. It was generated through the bulk and pedigree methods for six years, and then designated as "Iksan370" after a two-year advanced yield trial test. This variety was designated the name "Taejoong" after a regional yield trial test in eight locations throughout Korea for three years from 2014 to 2016. Its heading date was April 27 in upland and paddy filed conditions, and its maturity date was June 7 in uplands and June 4 in paddy fields, which were late compared to that of “Keumkang”. “Taejoong” had 417 spikes per m2, which was 300 less than that of “Keumkang”. However, the spike length was 13.4 cm and the number of kernel per one spike was 48, which was 5.8 cm longer and 19 higher than those of “Keumkang”, respectively. “Taejoong” showed strong resistance to lodging and moderate resistance to Fusarium head blight, but was susceptible to powdery mildew. “Taejoong” flour yield (71.8%) and flour lightness (91.90) were similar to those of “Keumkang”, but its protein content (11.1%), gluten content (8.8%), and sodium dodecyl sulfate-sedimentation volume (34.2 ml) were lower. These result showed that the flour dough strength of “Taejoong” was weaker than that of “Keumkang”. The high-molecular-weight gluten subunit compositions of "Taejoong" were Glu-A1 (N), Glu-B1 (7+9), and Glu-D1 (2+12). The granule-bound starch synthase compositions were Wx-A1, Wx-B1, and Wx-D1. The puroindoline compositions were Pina-D1 (a type) and Pinb-D1 (b type). The average grain yield of “Taejoong” in a regional yield trial was 5.3 ton/ha in uplands and 4.6 ton/ha in paddy fields, which were 21% and 13% higher than that of the reference cultivar, “Keumkang”, respectively. KCI Citation Count: 8